Uji Aktivitas Antibakteri Ekstrak Petis Udang terhadap Escherichia Coli dan Staphylococcus Aureus Menggunakan Metode Paper Disk - Aisha Noviadianty; Ardi Mustakim (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2025)
This study aims to evaluate the antibacterial activity of shrimp paste extract against Escherichia coli (Gram-negative) and Staphylococcus aureus (Gram-positive) using the paper disk method. The shrimp paste was extracted using ethanol as a solvent and tested for its inhibitory effect on bacterial growth through paper disks infused with various concentrations of the extract. The results showed that the shrimp paste extract exhibited antibacterial activity against both bacterial species, with varying inhibition zone diameters depending on the concentration used. Higher antibacterial activity was observed against Staphylococcus aureus compared to Escherichia coli, indicating that shrimp paste has potential as a natural antibacterial agent, particularly against Gram-positive bacteria. These findings support the utilization of fishery by-products such as shrimp paste as an eco-friendly alternative source of natural antibacterial agents.